Organizational and Legal Aspects of Public Services Delivery in the Republic of Kazakhstan - ZHANUZAKOVA, Leila; DOSSANOVA, Meruyert; TAZABEKOV, Muslim; MUKHAMEJANOV, Eduard (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
The article considers the specific features of public services delivery in the Republic of Kazakhstan and other countries where public services are provided with the involvement of different models of electronic government. Today, state provision of public services to citizens is becoming one of the most important spheres of the functioning of government authorities. The notion of public services has become an object of focused scientific research relatively recently in the Republic of Kazakhstan, while in developed countries, the relationship between the state and society, where the state is viewed as a service provider, developed in the 1980–1990s. The aim of this paper is to analyze the current state of the sphere of public services provided to the population of the Republic of Kazakhstan and to study international experience in this area. The authors view public services delivery as a process of information interaction between the state and society, which, at the current stage of IT development, is increasingly taking an electronic form. The authors explore historical and theoretical prerequisites for the creation of the modern system of public services, the current state of the corresponding organizational and legal framework in the Republic of Kazakhstan, and international experience of development and implementation of successful patterns of public services delivery. Besides, the authors study the specific features of legal regulation pertaining to handing public services over to a competitive environment. The article assesses the possibilities of further use of advanced technologies to address the tasks for which this important element of government control has been developed. The results obtained by the authors consist in the validation of the conclusions about the assessment of the public services sphere and its organizational and legal grounds, as well as the potential for its further development. The paper includes several suggestions for improvement of the organizational and legal framework of public services delivery. The novelty of this article consists in the fact that the authors suggest ways of further development of the interaction between the state and society based on thorough analysis of world practices of public services delivery